STRENGTHENING A CHILD-FRIENDLY ENVIRONMENT THROUGH IMPROVING YOUTH PROSOCIAL BEHAVIOR IN THE VILLAGE AREA OF GUNUNG ANYAR SURABAYA - Yuni Sufyanti Arief; Nuzul Qur'aniati; Ilya Krisnana; Iqlima Dwi Kurnia; Praba Diyan Rachmawati (Universitas Airlangga, 2022)
Introduction: The stages of adolescent development as one of the tasks of human development also have a role, one of them is applying prosocial behavior. Prosocial behavior is any form of behavior that has positive consequences for others, whether in the form of material, physical or psychological but has no clear advantage for the owner. The purpose of this community service is to improve knowledge and skills about prosocial behavior to adolescents in the village area of Gunung Anyar, Surabaya. so that it can develop adolescent prosocial behavior and can prevent antisocial behavior. Methods: The method used in this community service activity is training with lecture and case discussions methods about prosocial behavior in adolescents and peer group support. As many as 30 people consisting of 15 adolescent, 13 parents, and 2 health cadres, with the criteria of adolescent aged 13-18 years took part in this activity and an evaluation was also carried out by filling out a questionnaire on the prosocial behavior of adolescents, parents, and health cadres through pretest and posttest. Results: The results achieved through this activity were increase in prosocial behavior in adolescents, parents and health cadres. This is because the methods of lectures and case discussions can provide a clear experience in implementation prosocial behavior so that participants know and can apply skills in prosocial behavior in a community environment. Conclusion: The next community service activity requires the formation of youth health cadres with a broader goal of improving a child-friendly environment.